Host-Modulation Therapy and Chair-Side Diagnostics in the Treatment of Peri-Implantitis - Timo Sorsa; Joseph Bacigalupo; Mauno Könönen; Pirjo Pärnänen; Ismo T. Räisänen (Biosensors, 2020)
Previous studies report periodontitis and peri-implantitis being able to induce systemic low-grade inflammation, which is known to be associated with increased risk for some systemic medical disease such as cardiovascular disease. In this regard, recent studies have shown that host modulation therapy (HMT) together with traditional mechanical and surgical treatment not only cease the progression of periodontitis but also reduce the systemic collagenolytic biomarkers in both oral fluids and circulation. This suggests that the corresponding adjunctive HMT-medication could be effective in the prevention and treatment of dental peri-implantitis, as well. Furthermore, low-cost, safe, and practical oral fluid active matrix metalloproteinase-8 (aMMP-8) lateral-flow immunotests have been proposed as point-of-care/chair-side diagnostic tools to detect peri-implantitis and periodontitis, and to monitor their effective resolutions, while using various therapeutic strategies, including host modulation. This study reports the potential benefits of HMT-medication in the prevention and treatment of dental peri-implantitis among five patients (four of five were current/ex-smokers). In addition, the aMMP-8 point-of-care test diagnosed 20 peri-implantitis and 20 healthy controls correctly. In conclusion, this study and previous studies support the potential effectiveness of HMT-medication(s) and point-of-care/chair-side technologies in the treatment and diagnostics/monitoring of peri-implantitis. However, more studies are needed to further confirm this.